2018
DOI: 10.1073/pnas.1805351115
|View full text |Cite
|
Sign up to set email alerts
|

HSP90 is a chaperone for DLK and is required for axon injury signaling

Abstract: Peripheral nerve injury induces a robust proregenerative program that drives axon regeneration. While many regeneration-associated genes are known, the mechanisms by which injury activates them are less well-understood. To identify such mechanisms, we performed a loss-of-function pharmacological screen in cultured adult mouse sensory neurons for proteins required to activate this program. Well-characterized inhibitors were present as injury signaling was induced but were removed before axon outgrowth to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 73 publications
2
28
0
Order By: Relevance
“…However, many defects of Phr mutants remain in Phr1; Dlk double KO animals (Bloom et al 2007), which is also consistent with findings in invertebrates that PHR proteins have roles in addition to regulating DLK stability (Grill et al 2016). Besides being negatively regulated by PHR, DLK stability can be regulated by the chaperone heat shock proteins under stress and injury (Daviau et al 2006, Karney-Grobe et al 2018 (Figure 2c). Whether PHR regulates LZK remains unknown.…”
Section: Vertebrate Dlk and Lzksupporting
confidence: 86%
“…However, many defects of Phr mutants remain in Phr1; Dlk double KO animals (Bloom et al 2007), which is also consistent with findings in invertebrates that PHR proteins have roles in addition to regulating DLK stability (Grill et al 2016). Besides being negatively regulated by PHR, DLK stability can be regulated by the chaperone heat shock proteins under stress and injury (Daviau et al 2006, Karney-Grobe et al 2018 (Figure 2c). Whether PHR regulates LZK remains unknown.…”
Section: Vertebrate Dlk and Lzksupporting
confidence: 86%
“…These substances ensure that there is almost no Schwann cell death after axonal injury(Murai et al., 2016). Scott et al found that heat shock protein 90 (HSP90) is required as a chaperone for DLK for signalling during axonal injury, and they observed that HSP90 inhibitors strongly promote axonal growth(Karney‐Grobe et al., 2018). The studies mentioned above indicate that the response to axonal injury plays an important role in the repair of damaged peripheral nerves by melatonin.…”
Section: Discussionmentioning
confidence: 99%
“…JNK-mediated feedback phosphorylation of DLK correlates with an increase in DLK protein stability following TD (Huntwork-Rodriguez et al 2013). However, this initial report found that the change in DLK stability only became significant at prolonged times (8h) after TD, and others reported that DLK is stable in DRG neurons over this same 8h timeframe (Karney-Grobe et al 2018). These findings raised the possibility that JNK-mediated feedback phosphorylation of DLK might instead affect some other aspect of DLK-JNK signaling.…”
Section: Resultsmentioning
confidence: 92%